Transmission Line Models for Real-Time Mode Estimation Based on Synchronized Vector Measurements - Balametov, A.B. (Herald of Azerbaijan Engineering Academy, 2022)
The dispatch control centers received information about the power system mode from the Supervisory Control and Data Acquisition (SCADA) system, and from Phasor Measurement Units (PMU) in the form of telemetry and TV signals. Telemeasurements include information about the mode parameters. Traditionally, the EHV transmission line is presented in the form of a -scheme, the results of which have methodological modeling errors. Representation of overhead lines in the form of equations with distributed parameters makes it possible to obtain the highest accuracy. These equations contain hyperbolic functions and, in real-time simulation, slow down the performance. The choice of an adequate mathematical model of overhead lines of the corresponding accuracy of synchronized vector measurements in real time when assessing the state is important. The article discusses the models of overhead lines by equations with distributed parameters, -circuit, equivalent -circuit and chain -circuits, depending on the number of links. The results of calculating mode in terms of modeling accuracy are compared using the example of a 500 kV overhead line.